Cold atoms meet lattice gauge theory - Aidelsburger, Monika; Barbiero, Luca; Bermudez, Alejandro; Chanda, Titas; Dauphin, Alexandre; González-Cuadra, Daniel; Grzybowski, Przemysław R.; Hands, Simon; Jendrzejewski, Fred; Jünemann, Johannes; Juzeliūnas, Gediminas; Kasper, Valentin; et al. (Philosophical transactions of the Royal Society. A, Mathematical, physical and engineering sciences, 2022)
The central idea of this review is to consider quantum field theory models relevant for particle physics and replace the fermionic matter in these models by a bosonic one. This is mostly motivated by the fact that bosons are more ‘accessible’ and easier to manipulate for experimentalists, but this ‘substitution’ also leads to new physics and novel phenomena. It allows us to gain new information about among other things confinement and the dynamics of the deconfinement transition. We will thus consider bosons in dynamical lattices corresponding to the bosonic Schwinger or - Z - 2 - Z2 - Bose-Hubbard models. Another central idea of this review concerns atomic simulators of paradigmatic models of particle physics theory such as the Creutz-Hubbard ladder, or Gross-Neveu-Wilson and Wilson-Hubbard models. This article is not a general review of the rapidly growing field—it reviews activities related to quantum simulations for lattice field theories performed by the Quantum Optics Theory group at ICFO and their collaborators from 19 institutions all over the world. Finally, we will briefly describe our efforts to design experimentally friendly simulators of these and other models relevant for particle physics. - - This article is part of the theme issue ‘Quantum technologies in particle physics’.